Disruption of protein-protein interfaces: in search of new inhibitors - Mangani, Stefano (Springer, 2013)
This book examines the present and future of drug discovery at protein-protein interfaces. It details computational and experimental tools used in the field, and offers examples of drug-like molecules effective in interacting at protein-protein interfaces.